Pengaruh Strategi Limited edition Product (Scarcity Effect) Dan Fear of Missing Out (FOMO) Terhadap Impulsive Buying Behavior Dengan Hedonic shopping motivation Sebagai Variabel Mediasi (Studi Pada Konsumen Rucas di Kota Malang) - Nada Salsabila Sofia; Siti Asiyah; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2026)
Abstract The increasing competition in the fashion industry encourages companies to implement marketing strategies that influence consumer behavior, particularly impulsive buying. This study aims to examine the effect of limited edition strategy and Fear of Missing Out (FOMO) on impulsive buying behavior, with hedonic shopping motivation as a mediating variable among Rucas consumers. This research employs a quantitative approach using a survey method. Data were collected from 72 respondents through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS).The results indicate that the limited edition strategy does not have a significant direct effect on impulsive buying behavior, while FOMO has a positive and significant effect on impulsive buying behavior. Furthermore, both limited edition strategy and FOMO have a positive and significant influence on hedonic shopping motivation. Hedonic shopping motivation also has a positive and significant effect on impulsive buying behavior. In addition, hedonic shopping motivation significantly mediates the relationship between limited edition strategy and impulsive buying behavior, as well as between FOMO and impulsive buying behavior. These findings suggest that emotional factors play a crucial role as a mechanism linking marketing stimuli to consumer behavioral responses.The implications of this study indicate that scarcity-based marketing strategies and psychological pressure will be more effective in encouraging impulsive purchases when they enhance consumers’ emotional experiences and enjoyment during shopping activities. Keywords: Limited edition, Fear Of Missing Out, Hedonic shopping motivation, Impulsive Buying Behavior, SEM-PLS